1990
DOI: 10.1177/0310057x9001800207
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Pharmacokinetics of Interpleural Bupivacaine in Patients after Cholecystectomy

Abstract: Venous plasma concentrations ofbupivacaine were determined in eight cholecystectomy patients following multiple interpleural bolus instillations of bupivacaine 20 ml O.S% with adrenaline (S mgll) administered at six-to eight-hour intervals. The mean steady-state peak plasma concentration was 2.3 mgll (range 1.2-3.1 mgll); however, in three of the eight patients peak plasma concentrations were greater than 3 mgll. The mean accumulation ratio was found to be 1.6 (range 0.99-2.49), with steady-state occurring wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…There remains a discrepancy between our data and that of Seltzer and colleagues (1987), who reported a shorter half-life and higher values of clearance and steady-state volume of distribution following single bolus interpleural injections of bupivacaine in cholecystectomy patients. Previously, we had attributed this discrepancy to a difference in technique and suggested that prolonged absorption of bupivacaine from the pleural cavity may have contributed to the kinetic differences found in our studies (Kastrissios et al, 1990;Mogg et al, 1990). However, since the present results from continuous infusion confirmed those from our previous bolus dose studies, this now appears less likely and our results may reflect a decrease in the elimination of the drug in patients with biliary disease.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…There remains a discrepancy between our data and that of Seltzer and colleagues (1987), who reported a shorter half-life and higher values of clearance and steady-state volume of distribution following single bolus interpleural injections of bupivacaine in cholecystectomy patients. Previously, we had attributed this discrepancy to a difference in technique and suggested that prolonged absorption of bupivacaine from the pleural cavity may have contributed to the kinetic differences found in our studies (Kastrissios et al, 1990;Mogg et al, 1990). However, since the present results from continuous infusion confirmed those from our previous bolus dose studies, this now appears less likely and our results may reflect a decrease in the elimination of the drug in patients with biliary disease.…”
Section: Discussionsupporting
confidence: 62%
“…The interpleural infusion regimen was determined empirically from pharmacokinetic data derived in our previous studies in order to produce a steady-state venous plasma concentration of 2 mg 1-1 (Kastrissios et al, 1990;Mogg et al, 1990). This concentration was chosen since it was representative of the mean steadystate drug concentration (2.3 ± 0.7 mg l-1) previously measured (Kastrissios et al, 1990) after intermittent interpleural administration of 20 ml doses of 0.5% bupivacaine HCl with adrenaline, the most commonly employed clinical dosage regimen.…”
Section: Infusion Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies demonstrate an acceptable safety profile with bupivacaine administered via the interpleural route [6, 8, 12–14, 16, 19]. In our study we used a conservative dosing regime and found no reported symptoms consistent with local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 66%